The Effect of Radiation on Secondary Sex Ratio among Radiologists in Shiraz, Iran - Mahnaz Yadollahi; Mohammad Farahmand; Mehrdad karajizadeh; Haleh Ghaem; Maryam Foadi; Narges Shamseddini (Iranian Journal of Health, Safety and Environment, 2018)
Environmental and occupational exposure may play a role in gender offspring. This study aimed to investigate the effect of radiation on gender ratio in the offspring of radiologists and technicians. This cross-sectional study was conducted on 262 participants with a total of 354 children. A data collection form including age, years spent in radiology practice, number of children, sex of each child, observance of radiation protection principles, and intensity of exposure based on International Commission Radiological Protection was completed. Male to female ratio was calculated 0.85 in fathers and 0.75 in mothers in comparison to this ratio estimated in Iran demographic statistics sex ratio which is 1.03. Highly-exposed parents (Prevalence ratio [PR]: 1.67, 95% confidence interval [CI]: 1.11-2.52), as well as fathers (PR: 2.72, 95%CI: 1.56-4.72), had a significant propensity to have female offspring. However, this criterion in female radiologists was not found to be significant (P= 0.57). Moreover, in fathers a significant relationship was found between the years spent in radiology field up to the time of the child’s birth or age of the parents’ at child’s conception with offspring gender (4-6 year: PR: 2.07, 95% CI: 1.15-3.72; ≥7 year: PR:1.81, 95%CI: 1.18-2.78). Highly-exposed radiology male personnel, as well as those exposed to radiation 4 years or more before the offspring’s birth, were more likely to have daughters than sons. Although no exact mechanism has been identified for this preponderance, further animal studies are required to evaluate whether x ray is an influential factor in offspring gender.